Efficacy of antidepressants and benzodiazepines in minor depression: systematic review and meta-analysis. - Barbui, C; Cipriani, A; Patel, V; Ayuso-Mateos, J; van Ommeren, M (2011)
BACKGROUND: Depression is a common condition that has been frequently treated with psychotropics. AIMS: To review systematically the evidence of efficacy and acceptability of antidepressant and benzodiazepine treatments for patients with minor depression. METHOD: A systematic review and meta-analysis of double-blind randomised controlled trials comparing antidepressants or benzodiazepines v. placebo in adults with minor depression. Data were obtained from MEDLINE, CINAHL, EMBASE, PsycInfo, Cochrane Controlled Trials Register and pharmaceutical company websites. Risk of bias was assessed for the generation of the allocation sequence, allocation concealment, masking, incomplete outcome data, and sponsorship bias. RESULTS: Six studies met inclusion criteria. Three studies compared paroxetine with placebo; fluoxetine, amitriptyline and isocarboxazid were studied in one study each. No studies compared benzodiazepines with placebo. In terms of failures to respond to treatment (6 studies, 234 patients treated with antidepressants and 234 with placebo) no significant difference between antidepressants and placebo was found (relative risk (RR) 0.94, 95% CI 0.81-1.08). In terms of acceptability, data extracted from two studies (93 patients treated with antidepressants and 93 with placebo) showed no statistically significant difference between antidepressants and placebo (RR=1.06, 95% CI 0.65-1.73). There was no statistically significant between-study heterogeneity for any of the reported analyses. CONCLUSIONS: There is evidence showing there is unlikely to be a clinically important advantage for antidepressants over placebo in individuals with minor depression. For benzodiazepines, no evidence is available, and thus it is not possible to determine their potential therapeutic role in this condition.